PROMOTING FOOD SECURITY VIA CONTROLLING TOMATOES MARKETABILITY BY USING RNAi TECHNOLOGY, PECTIN AND ORGANIC CALCIUM - Maryam S. Elias,; Kadhim D. H. Al-Jubouri,; Khalil A. Saeed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
RNAi gene silencing was performed by utilizing pectate lyase, an enzyme capable of degrading pectin, in conjunction with subsequent pectin (organic waste) and organic calcium treatment, allowing for prolonged retention of tomatoes on the plant without compromising quality traits. The study was conducted at two locations using a randomized complete block design (RCBD) and consisted of nine treatments. Results showed that SlPL-RNAi plants had the most fruit firmness and Mesocarp thickness; with values of 13.1 kg/cm² and 167.5 µm, respectively, followed by the CaP1P2 treatment (8.56 kg/cm² and 117.0 µm).  SlPL-RNAi fruits also showed higher calcium and pectin contents and lower polygalacturonase (PG) activity, which were associated with firmer fruits and prolonged on-plant period (from pink stage to spoil, 33.7 days). Likewise, the CaP1P2 application increased the thickness and firmness of the tissue with a shelf life of up to 20 days. These advancements were credited to increased levels of calcium and pectin along with inhibited action of ripening- associated enzymes. This study provides a useful incorporation of RNAi and biochemical treatments as effective approaches to induce postharvest loss and promote food and environmental sustainability.